PENGARUH KUALITAS PENGADUAN, KECEPATAN PENANGANAN DAN KEPUASAN PENGGUNA TERHADAP EFEKTIVITAS FITUR PENGADUAN PLN MOBILE UP3 CIKOKOL - Christover, Jean; Djati, Sunding Pantja; Mariam, Siti; Mahadewi, Erlina Puspitaloka (POLITEKNIK LP3I JAKARTA, 2026)
In the digital era, public services have transformed through applications such as PLN Mobile. The effectiveness of its complaint feature is influenced by complaint quality, handling speed, and user satisfaction, with digital literacy serving as a moderator. This study aims to analyze the factors affecting the effectiveness of the complaint feature on the PLN Mobile application within the PLN UP3 Cikokol working area.Using purposive sampling, the study involved 120 respondents who are customers of PLN UP3 Cikokol. Data analysis was performed using PLS-SEM with smartpls 4 software. The results indicate that complaint quality, handling speed, and user satisfaction significantly influence complaint feature effectiveness. Notably, complaint quality has the strongest impact on user satisfaction compared to other relationships in the model. Furthermore, digital literacy does not significantly moderate the influence of complaint quality, handling speed, or user satisfaction on feature effectiveness. This suggests that the PLN Mobile complaint feature is sufficiently inclusive, ensuring its effectiveness is accessible to all users regardless of their digital proficiency levels.